2009
DOI: 10.1002/jsfa.3570
|View full text |Cite
|
Sign up to set email alerts
|

Use of rosemary and Hibiscus sabdariffa in production of kavurma, a cooked meat product

Abstract: BACKGROUND: Spices are used in different types of foods to improve flavours and are well known for their antioxidant properties. The objective of this study was to determine the effects of rosemary and Hibiscus sabdariffa on the quality attributes of kavurma, a cooked meat product. RESULTS: pH values of samples remained constant (P > 0.05) at about 6.35 during the cooking period, and addition of H. sabdariffa, rosemary or butylated hydroxytoluene (BHT) did not significantly affect pH values (P > 0.05). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
5
20
0
1
Order By: Relevance
“…The L values found in the present experiment were in agreement with those reported by Bozkurt & Belibagl (2009) that addition of roselle increased ligthness value of kavurma. However, Bozkurt & Belibagl (2009) found that roselle did not affect L value of sucuk.…”
Section: Color Determinationsupporting
confidence: 93%
See 4 more Smart Citations
“…The L values found in the present experiment were in agreement with those reported by Bozkurt & Belibagl (2009) that addition of roselle increased ligthness value of kavurma. However, Bozkurt & Belibagl (2009) found that roselle did not affect L value of sucuk.…”
Section: Color Determinationsupporting
confidence: 93%
“…The result about the yellowness (b) values of se'i found in this experiment was similar to that reported by Bozkurt & Belibagl (2009) that the addition of roselle could reduce yellowness values of kavurma. The decrease in yellowness values suggested that the color of se'i turned to blue rather than yellow.…”
Section: Variablessupporting
confidence: 91%
See 3 more Smart Citations